USING THE SOUTH AFRICAN EXCELLENCE MODEL TO FOCUS IMPROVEMENT STRATEGIES IN SOUTH AFRICA. - Smit, Bruce R (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: South African companies wish to join the world class family. As the Malcolm Baldrige Quality Award in the USA and the European Quality Award in Europe have been effected, the South African Quality Institute (SAQI) pioneered and developed a National Quality Award together with leading South African companies. The South African Award model is a full hybrid of the Malcolm Baldrige and European Foundation Quality models. The awards process is now managed by the South African Excellence Foundation. This model enables companies to assess their excellence levels and use benchmarks towards improved quality, service and costs. The model has been ratified by the administrators of both of the aforementioned awards. The criteria in the award lend themselves to measurement by self assessment. This paper explains the model and its application as a foundation to strategic planning. AFRIKAANSE OPSOMMING: Maatskapye in Suid Afrika moet op die wereldmark kan presteer. Amerika het die Malcolm Baldrige Kwaliteitstoekenning en Europa die Europese Kwaliteitstoekenning.vir uitmuntende prestasie in die besigheidswereld daargestel. Die Suid Afrikaanse Kwaliteitsinstituut (SAQI) het in 1997 'n Suid Afrikaanse eweknie ontwikkel. Die Suid Afrikaanse Kwaliteitstoekenning is deur die administrateurs van eersgenoemde pryse aanvaar. Die lokale Kwaliteitstoekennings word tans deur die Suid Afrikaanse Uitmuntentheidfondasie geadministreer. Die Kwaliteitstoekenning model kan gebruik word am self-meting toe te pas met die doel om besigheids prestasie te verbeter. Hierdie geskrif stel die Suid Afrikaanse model daar stel en verduidelik hoe dit vir strategiese beplanning toegepas kan word.